A critical assessment of NHESP’S contribution to the Malaysian economy - Md Zain, Ahmad Nurulazam; Abdullah, Nur Anisah; Mat Ghani, Gairuzazmi; Mohd Arshad, Mohd Nahar; Khalid, Haniza; Zulkifli, Izyani (IPPTN, 2014)
A critical assessment of NHESP’S contribution to the Malaysian economy